Zonificación De Amenaza Por Incendios De La Cobertura Vegetal (Icv) En El Municipio De Melgar-Tolima A Escala 1:25.000 (2025)
This study analyzes the fire threat to plants cover of Melgar, Tolima, using Geographic Information Systems (GIS) at a 1:25000 scale. The objectives focused on evaluating the historical frequency of fires, ignition factors, and the zoning of áreas in threatened condition. It was carried out based on the IDEAM (2011) methodology, incorporating factors such as vegetation susceptibility, climate, topography and accessibility. The results show that 48,64% of área presents a Moderate threat level, 34,47% High and 4,95% Very High.